Measuring efficiency in english maintained secondary schools : techniques, policy implications and practicalities - Pigg, Darren (2015)
This article describes the work that has been undertaken by the Department for Education and Skills in England to construct and utilise school level efficiency measures for all maintained secondary schools in England. The Department is using Data Envelopment Analysis techniques to generate efficiency estimates, to both identify where .current best practice exists and also to bolster the ability of less efficient schools to benchmark themselves against other "similar" peer schools.